Building performance simulation for sensemaking in architectural pedagogy - Martha Bohm (Buildings & Cities)
During sensemaking one constructs meaning from one’s chaotic surrounding information; cues are extracted and attended to such that action is possible. Within architecture, making sense of quantitative information (e.g. carbon emissions) can facilitate climate responsiveness from early stages of building design. This paper posits that building performance simulation (BPS) can be a tool to nurture so-called ‘spatial-data sensemaking’ within architectural training; the pedagogy must manage uncertainty so students can make sense of performance data during design. This teaching method was used in an undergraduate architecture class. Students used BPS to design buildings, using visual audits to build trust in the results about performance; precision was downplayed in favor of actionable information. A qualitative analysis of these architectural students’ reflections (n = 104) is presented to shed light on how they construct understandings of BPS. Results suggest that students deepened their understanding of building–energy relationships, and refined their intuition, especially about interrelationships and trade-offs. They understood BPS to be a tool providing useful information, especially the visual, through experimentation to support design decision-making and argumentation, and ultimately for effecting change in architectural practice. Practice relevance This paper contributes to a broader discussion of BPS in teaching, and the debate whether students should be BPS ‘performers’ or ‘consumers,’ by providing insight into the student perspective of the learning process. The results describe student perceptions of their own knowledge and abilities, and their understandings of BPS. The findings support the ‘performer’ paradigm of BPS instruction by demonstrating that the technical work of BPS analysis leads to making sense of an emerging design. More broadly, the results align with theories viewing architecture as a reflective practice whereby students learn to design through thoughtful engagement with the results of their design choices. The novelty of this paper lies in its assessment of the student experience and perception of BPS instruction within their design practice. This paper is one of very few to assess the student perspective on BPS instruction rather than emphasize instructor intentions or describe student output.